Keterlibatan Elit Lokal dalam Peningkatan Partisipasi Politik pada Pemilihan Bupati dan Wakil Bupati Kabupaten Toraja Utara Tahun 2015 - Muhammad Fadli; Muh. Kausar Bailusy; Jayadi Nas; Achmad Zulfikar (ARISTO, 2018)
This research aims to illustrate and analyze the role of local elites in increasing voter participation and impact of local elite involvement in North Toraja District Head Vice Regent and Vice Regent 2015 by using qualitative descriptive method. Data were obtained by using interviews as well as literature and document studies.The results indicate that local elites play a role in increasing participation in Pilkada in North Toraja according to their capacity. Local political elites socialize candidate pairs, become campaign teams and volunteer teams of candidates for regent / vice bupati candidates. Religious figures become part of the election organizers and socialize the implementation of Pilkada through religious activities. Adat leaders play a role by utilizing the charisma owned socialize information Pilkada to the community, build communication with the candidate pair then support it in the elections.The involvement of local elites in the implementation of North Sulawesi District Head Vice Regent and Vice Regent 2015 has a significant impact on the political participation of the community. Increasing the political participation of the people in Pilkada is not solely because of the involvement of local elites in disseminating information on Regional Head Election. However, there are other motivating factors that enable the community to actively participate, namely (1) to be given material rewards (including piloting gambling activities) and (2) the religious sentiments of one of the candidate pairs on religious leaders in worship activities.